2018
DOI: 10.1002/csr.1514
|View full text |Cite
|
Sign up to set email alerts
|

CEOs' regulatory focus, slack resources and firms' environmental innovation

Abstract: To synthesize the literature on upper echelons theory, regulatory focus theory and the resource-based view, this study examined the relationship of CEOs' regulatory focus, slack resources and firms' environmental innovation. Through the investigation of 191 manufacturing firms in China, we found that a CEO's promotion focus had a positive influence both on the firm's environmental processes and on product innovation, while a CEO's prevention focus had a negative influence. In addition, slack resources moderate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 56 publications
2
46
0
1
Order By: Relevance
“…To reduce costs, companies implement green practices by reducing waste in terms of materials and energy. Managers have the power to directly influence a company's engagement in green practices through developing corporate strategy and trying to improve financial performance (Liao & Long, 2018). More companies are willing to follow sustainability guidelines to improve their reputation.…”
Section: Green Motives and Green Value Co-creationmentioning
confidence: 99%
“…To reduce costs, companies implement green practices by reducing waste in terms of materials and energy. Managers have the power to directly influence a company's engagement in green practices through developing corporate strategy and trying to improve financial performance (Liao & Long, 2018). More companies are willing to follow sustainability guidelines to improve their reputation.…”
Section: Green Motives and Green Value Co-creationmentioning
confidence: 99%
“…As an environmental protection strategy and a demonstration of firms' sense of responsibility to the environment, environmental innovation has been a major subtopic of environmental study. Currently, there is much research being done on the impact of existing institutions (Ghisetti & Pontoni, 2015; Marin & Zanfei, 2019), stakeholders (Huang, Hu, Liu, Yu, & Yu, 2016), senior management (Liao & Long, 2018), and resources (Cainelli, De Marchi, & Grandinetti, 2015) on environmental innovation and the impact of environmental innovation on firms' performance (Andries & Stephan, 2019; Doran & Ryan, 2016) and competitive advantage (Liao, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The greater the level of resource slack owned by the company, the greater the company's ability to improve positive performance (Cyert & March, 1963;Bourgeois, 1981;Chen, 2008;Iyer & Miller, 2008;Lin et al, 2009). Liao & Long (2018) found that slack resources had a positive influence on environmentally friendly product innovations in selecting company CEOs. Furthermore, this positive effect also directs slack resources help the company to succeed in every environmental change (Liao & Long, 2018).…”
Section: Slack Resourcesmentioning
confidence: 99%
“…Liao & Long (2018) found that slack resources had a positive influence on environmentally friendly product innovations in selecting company CEOs. Furthermore, this positive effect also directs slack resources help the company to succeed in every environmental change (Liao & Long, 2018).…”
Section: Slack Resourcesmentioning
confidence: 99%